Long-term performance of a hybrid indirect evaporative cooling-mechanical vapor compression cycle: A case study in Saudi Arabia - Chen, Qian; M, Kum Ja; Burhan, Muhammad; Shahzad, Muhammad Wakil; Ybyraiymkul, Doskhan; Oh, Seungjin; Cui, Xin; Ng, Kim Choon (Frontiers in Built Environment, 2022)
In Saudi Arabia, air conditioning is the main consumer of electricity, and increasing its energy efficiency is of great importance for energy conservation and carbon footprint reduction. This study presents the evaluation of a hybrid indirect evaporative cooling-mechanical vapor compression (IEC-MVC) cycle for cooling applications in Saudi Arabia. The annual demand for cooling and dehumidification in main cities are quantified. Most cities are characterized by a high sensible cooling demand, and a few cities near the coasts of Red sea and Persian Gulf also have a need for dehumidification. Daily analysis reveal that IEC can undertake ~60% of the cooling load in the summer of arid cities, and the energy consumption can be reduced by up to 50%. The contribution of IEC and the energy saving are less significant in humid cities because the latent loads have to be handled by MVC. Over the whole year, IEC contributes 50% of the total cooling load and reduce the energy consumption by 40% in dry cities, while the saving is lower at 15-25% in humid cities like Mecca and Jeddah. The average water consumption of the IEC is in the range of 4-12 L/hr. The water consumption be replenished by the condensate collected from the MVC evaporator if the ambient humidity is high. Based on the annual performance, the annual cost of the IEC-MVC process is calculated, and it is 15-35% lower than the standalone MVC. The results demonstrate great potential of the hybrid IEC-MVC cycle in Saudi Arabia.